Neglected domain of feminism in medical education: The need for curricular reform - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Current Medical Issues, 2022)
Feminism can be acknowledged as a kind of movement to bring about an end to sexism, sexist exploitation, and domination of the male gender. The necessity to bring about an improvement in the health and well-being of women originated 4–5 decades ago, owing to the rising awareness about gender bias in a male-dominated medical community. This means that we continue to deliver medical education and produce medical students, wherein the training is still rooted in patriarchy, with the perspectives of women significantly being ignored. Further, most of the medical textbooks had limited content on women's gender-specific knowledge, and thus it was envisaged by some of the educationists to adopt specific corrective measures to minimize the imbalance and injustice. To conclude, the component of feminism in medical education has not been given due importance over the years. Thus, there is an indispensable need to address these components in the process of design, implementation, and evaluation of the curriculum to produce gender-sensitive medical graduates who play their part in overcoming different kinds of gender discrimination.